PP72 Does Investment in the Health Sector Promote or Inhibit Economic Growth?. (10th September 2013) - Reeves, A; Basu, S; McKee, M; Meissner, C; Stuckler, D
Abstract : Background: Is existing provision of health services in Europe affordable during the recession or could cuts damage economic growth? This debate centres on whether government spending has beneficial or perverse effects on economic growth. We assessed the return on government investment by estimating the "fiscal multiplier" (number of PPP dollars returned in economic growth for each PPP $1 government spending). Methods: Cross-national data on government expenditure among 25 EU countries from 1995 to 2007 were used to estimate fiscal multipliers using fixed-effects regression. Results: The multiplier for total government spending was 1.61 (95% CI 1.37, 1.86). Results ranged widely across sectors, from -9.8 for defence (-16.7, -3.0) and 0.06 for economic affairs including bailouts (-0.71, 0.84) to 2.9 for social protection spending (1.9, 3.8) and 4.3 for health (2.5, 6.1). The degrees of domestic absorption of investment explain these differences. Tradable components of government spending, like defence, are linked to significantly more negative trade balance (β = -2.87, p = 0.02), whereas non-tradable areas of the budget, including health and education, had no such association (peducation = 0.22; phealth = 0.21). Conclusion: Government spending on health may have short-term effects that make recovery more likely.